1995
DOI: 10.1001/archsurg.1995.01430120055008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Intestinal and Splenic Cytokines After Parenteral Nutrition

Abstract: Infusion of lipid-free PN induces a differential mRNA expression for inflammatory cytokines in the spleen and intestine with an overall up-regulation of the expression of inflammatory cytokines in the intestine and a down-regulation in the spleen. These data provide evidence that the regulatory mechanisms for cytokine production are different in the intestine and the spleen. Further study is needed to elaborate the mechanism of this differential expression following lipid-free PN infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
8
1
1
Order By: Relevance
“…Bacterial overgrowth in intestine is also a major etiologic factor in the development PNAC and several studies have shown the role of early and repeated sepsis on PNAC in infants [3,18,20]. The endotoxin and cytokines, such as TNF, IL-1 and IL-6, induce hepatotoxicity and downregulate the bile acid transporter gene expression, causing cholestasis [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial overgrowth in intestine is also a major etiologic factor in the development PNAC and several studies have shown the role of early and repeated sepsis on PNAC in infants [3,18,20]. The endotoxin and cytokines, such as TNF, IL-1 and IL-6, induce hepatotoxicity and downregulate the bile acid transporter gene expression, causing cholestasis [18].…”
Section: Discussionmentioning
confidence: 99%
“…The endotoxin and cytokines, such as TNF, IL-1 and IL-6, induce hepatotoxicity and downregulate the bile acid transporter gene expression, causing cholestasis [18]. Cholestasis itself increases the risk of sepsis, which induces further translocation of endotoxin [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a trend in changes is noted, these changes in mRNA expression are only semi-quantitative, and further quantitative studies will need to be performed to confirm these findings. Although cytokine expression has been previously reported to show an increase in interleukin 6 with TPN administration in rats, these investigators examined full-thickness biopsies of the intestine [20]. Thus, the origin of these cytokines may have come from a variety of sources and may not reflect changes occurring in the epithelial layer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the spleen and thymus are two important immune system organs in the body, their cell components are different, the main cells in the thymus being lymphocytes, whereas the spleen possesses large macrophages as well as lymphocytes. 21,22 It is speculated that TPN can induce atrophy of the thymus and suppress the lymphocyte function after severe injury, although the exact mechanism is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%